การพัฒนาระบบการเข้าถึงและให้บริการแท็กซี่เพื่อคนพิการบนระบบ Smartphone และ Web GIS กรณีศึกษา เมืองพิษณุโลก: Development of Accessibility and Taxi Service for Disabled Based on Smartphone and Web GIS: the Case Study of Phitsanulok Municipal - Choosumrong, Sittichai; Rachavong, Pathana; Kham-Chiangern, Amphawan (Asian Health, Science and Technology Reports, 2018)
การพัฒนาระบบแจ้งตำแหน่งและข้อมูลพื้นฐานสำหรับคนพิการเพื่อขอใช้บริการแท็กซี่ผ่านโทรศัพท์สมาร์ทโฟนมีจุดมุ่งหมายของการศึกษา คือ 1) เพื่อจัดทำระบบฐานข้อมูลผู้พิการแบบออนไลน์บนระบบอินเทอร์เน็ต 2) เพื่อจัดทำระบบแจ้งตำแหน่งและข้อมูลพื้นฐานสำหรับคนพิการเพื่อขอใช้บริการแท็กซี่ผ่านโทรศัพท์สมาร์ทโฟน โดยประชากรและกลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ ได้แก่ คนพิการ 3 ประเภท คือ คนพิการด้านร่างกายหรือการเคลื่อนไหว จำนวน 30 คน คนพิการด้านการมองเห็น จำนวน 30 คน และคนพิการด้านการได้ยินหรือการสื่อความหมาย จำนวน 20 คน ที่อาศัยอยู่ในเขตอำเภอเมืองพิษณุโลก และคนขับรถแท็กซี่ จังหวัดพิษณุโลก งานวิจัยนี้ ได้เก็บรวบรวมข้อมูล โดยการออกแบบแบบสอบถามและแบบสัมภาษณ์ สำหรับคนพิการ เพื่อใช้ในการสำรวจความต้องการเดินทางของคนพิการและทัศนคติที่มีต่อการขนส่งสาธารณะในเมืองพิษณุโลก ตลอดจนตำแหน่งที่อยู่อาศัยของคนพิการ และเก็บข้อมูลพิกัดของที่อยู่ของคนพิการในเขตอำเภอเมืองพิษณุโลกด้วยเครื่อง GPS จากนั้นทำการนำเข้าค่าพิกัดลงในโปรแกรม QGIS และนำข้อมูลเข้าสู่ระบบฐานข้อมูล PostgreSQL / PostGIS ซึ่งจะได้ฐานข้อมูลของคนพิการและฐานข้อมูลของตำแหน่งที่อยู่ของคนพิการ ข้อมูลจากการสัมภาษณ์โดยใช้แบบสอบถามความต้องการเดินทางของคนพิการและทัศนคติที่มีต่อการขนส่งสาธารณะในเมืองพิษณุโลก ด้านความต้องการการเดินทาง พบว่าคนพิการส่วนใหญ่มีการเดินทางโดยรถสาธารณะเป็นส่วนใหญ่ และแท็กซี่ก็เป็นหนึ่งในบริการที่คนพิการเลือกใช้บริการ ทัศนคติของคนพิการที่มีต่อการขนส่งสาธารณะ ความคิดเห็นของผู้พิการ ในด้านราคาค่าโดยสาร และพฤติกรรมของคนขับแท็กซี่ อยู่ในเกณฑ์ดี ราคาค่าโดยสารที่ผู้พิการสามารถจ่ายได้ ส่วนในด้านความปลอดภัยนั้น คนพิการมีความเห็นว่าการใช้รถสาธารณะส่วนใหญ่ไม่ค่อยมีความปลอดภัยเท่าที่ควร ระบบแจ้งตำแหน่งและข้อมูลพื้นฐานสำหรับคนพิการเพื่อขอใช้บริการแท็กซี่ผ่านโทรศัพท์สมาร์ทโฟน จัดทำขึ้นมาเพื่อจัดทำฐานข้อมูลของคนพิการ และ แจ้งตำแหน่งและเงื่อนไขต่างๆ สำหรับคนพิการเพื่อขอใช้บริการแท็กซี่ผ่านโทรศัพท์สมาร์ทโฟน ซึ่งการให้บริการนั้นจะผ่านทางMobile Web โดยอาศัยเครือข่ายอินเทอร์เน็ต ในส่วนของหน้าเว็บจะเป็นการลงทะเบียนก่อนใช้บริการและข้อมูลตำแหน่งที่อยู่ของคนพิการซึ่งเป็นข้อมูลที่ดึงมาจากฐานข้อมูล PostgreSQL เมื่อมีการใช้บริการผ่านโทรศัพท์สมาร์ทโฟนข้อมูลจะถูกส่งลงฐานข้อมูล PostgreSQLของศูนย์บริการแท็กซี่ จากการศึกษาแสดงให้เห็นว่าการพัฒนาระบบการสืบค้นและวิเคราห์ข้อมูลเชิงพื้นที่สามารถนำมาใช้งานได้ในชีวิตจริงได้เป็นอย่างดี จากตัวอย่างงานวิจัยนี้หากนำระบบไปพัฒนาต่อยอดและแจ้งข้อมูลสู่สาธารณะ จะสามารถสามารถช่วยเหลือคนพิการในการเดินทางโดยรถแท็กซี่ได้สะดวกมากยิ่งขึ้น ช่วยลดปัญหาในการเลือกรับผู้โดยสารที่เป็นคนพิการ ตลอดตนกับการค้นหาและบริการด้านต่างๆก็สามารถนำผลงานนี้ไปประยุกต์ได้ในอนาคต Development of Location and Information Service for Disabled Accessibility Taxi on demand System Based on Mobile Web GIS has the purposes of the study as follows: 1) to create online database system for people with disabilities on the internet 2) to create a system of the location and basic information for people with disabilities in using taxi service through smartphone. Population and subject used in this study including 3 types of people with disabilities , 30 of physical or movement , 30 of visual or blind and 20 of hearing impairment or interpretation disabilities in Amphoe Muang, Phitsanulok and taxi drivers in Phitsanulok. Data collected in this study by creating the questionnaire and the interview for people with disabilities to survey the need of traveling and the attitude toward the public transportation in the city of Phitsanulok as well as the location where they lived and the coordinates of the address of the people with disabilities in Amphoe Muang, Phitsanulok with the GPS. Then import the coordinates in the program by QGIS and apply the information to the system PostgreSQL / PostGIS. This will be the database for people with disabilities and the location address of the people with disabilities. The data from the interview by using the questionnaires in traveling of the people with disabilities and attitude toward the public transportation in the city of Phitsanulok found that people with disabilities are often travel by public transportation for the most, and taxi is one of the services that people with disabilities use the service. The attitude of the people with disabilities on the public transportation found that, the fare and taxi drivers’ behaviors are at good level, they can afford. As for the security, people with disabilities agreed that most of the public transportation are not safe enough. The system of the location and basic information for people with disabilities to use the taxi service through Smartphone was designed to create a database of the people with disabilities and inform the position and the conditions for people with disabilities to use the taxi service through Smartphone via Mobile web by using internet networks. In the section of the web page is the registered page before using the service and the location information which pulled from the PostgreSQL database of people with disabilities. When there is a service via the smartphone, data will be sent to a PostgreSQL database at the center taxi service. The development of searching and spatial analysis system can be used for the real life. The result of this research can continue developing and published to public that people can use this system to help disabilities people to travel by taxi. Moreover it can be reduced the problem in choosing the passengers as they were people with disabilities.